Personality Characteristics and Emotional Distress Among Chinese Pregnant Women: A Moderated Mediation Model - Yang, Wenjiao; Hou, Yanfei; Chen, Yu; Liu, Wenting; Fang, Fan; Xiao, Julan; Wang, Jing (Frontiers in Psychiatry, 2021)
Previous studies have suggested that certain personality characteristics are associated with emotional distress during pregnancy. However, the underlying mechanism of this association is rarely understood. The current study investigated the links between personality and pregnant women’s emotional distress (depressive and anxiety symptoms), tested the chain mediating effects of two resilience factors——social support and positive coping, and explored whether socio-economic status (SES) could moderate the effects (including direct and/or indirect effects) of personality on their emotional distress. Results of a relatively large sample of pregnant women in China (N = 1157) showed positive associations for psychoticism and neuroticism with depressive and anxiety symptoms as well as negative associations for extraversion with depression and anxiety. After controlling for four important variables (the first pregnancy or not, having adverse pregnancy experience or not, being pregnant as planned or not, and number of weeks of pregnancy), social support and positive coping acted as chain mediators on the associations of personality with depressive symptoms as well as of personality with anxiety. Overall, the association of personality and depressive symptoms demonstrated invariance across SES. However, SES moderated the relationship between personality and anxiety. Specifically, the negative association of positive coping with anxiety symptoms was weaker for low SES women than for high SES ones. Results highlight the importance of social support and positive coping to decrease personality-related depressive and anxiety symptom among pregnant women. Furthermore, identifying other resilience factors that alleviating anxiety in women with low SES is urgently called for.